2019
DOI: 10.3389/fpsyt.2019.00030
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Research in Depression: Principles, Challenges, and Open Questions

Abstract: Cytokines have been implicated in the pathology of depression. Currently, the evidence is based on cross-sectional studies and meta-analytic research comparing blood concentrations of T helper type 1 (TH1), T helper type 2 (TH2), pro-inflammatory or anti-inflammatory cytokines of patients with a depressive disorder to those of healthy controls. Additionally, multiple longitudinal studies have investigated cytokine levels during antidepressant treatment. According to the current literature, it seems that periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
167
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(181 citation statements)
references
References 212 publications
(212 reference statements)
3
167
1
10
Order By: Relevance
“…As discussed throughout the paper, the lack of reliable conclusions may be partly explained by limitations that this body of studies suffered from, including heterogeneity in design, duration, setting, features of the sample, statistical power, criteria and/or tools used to assess clinical symptoms or profiles, and the limited number of comparative studies testing the differential efficacy of specific antidepressants. In addition, it should be noted that our review focused only on a limited set of variables, while other individual/clinical factors, relatively easy to assess in clinical practice, may play a role, such as childhood maltreatment/adversities, [124][125][126] inflammatory markers, 127,128 other symptom profiles or individual features. Among the latter, alexithymia, reflecting difficulty with identifying and expressing emotions, seems to be associated with higher severity of depression, increased suicide risk, and pro-inflammatory imbalance; [129][130][131][132][133] thus its potential contribute to selection of specific antidepressant class/compound may be worth investigating.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed throughout the paper, the lack of reliable conclusions may be partly explained by limitations that this body of studies suffered from, including heterogeneity in design, duration, setting, features of the sample, statistical power, criteria and/or tools used to assess clinical symptoms or profiles, and the limited number of comparative studies testing the differential efficacy of specific antidepressants. In addition, it should be noted that our review focused only on a limited set of variables, while other individual/clinical factors, relatively easy to assess in clinical practice, may play a role, such as childhood maltreatment/adversities, [124][125][126] inflammatory markers, 127,128 other symptom profiles or individual features. Among the latter, alexithymia, reflecting difficulty with identifying and expressing emotions, seems to be associated with higher severity of depression, increased suicide risk, and pro-inflammatory imbalance; [129][130][131][132][133] thus its potential contribute to selection of specific antidepressant class/compound may be worth investigating.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, chronic stress and low-grade inflammation are believed to contribute to the pathophysiology of MDD 8 10 . In fact, patients with MDD express increased levels of proinflammatory cytokines like interleukin (IL)-1, IL-6 and tumor necrosis factor (TNF)-α in peripheral blood, which can access the central nervous system (CNS) and activate tissue-resident macrophages like microglia, impair HPA axis function, modulate monoaminergic neurotransmission, and reduce neural plasticity 11 13 . The tryptophan-kynurenine pathway links depression and inflammation, and under stressful and inflammatory conditions, microglial indoleamine 2,3-dioxygenase (IDO) activity reduces serotonin availability and results in the production of excitotoxic metabolites such as quinolinic acid 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In BV-2 microglia cells, IL-4, but not IL-10, re-directed LPS (lipopolysaccharide)-activated microglia towards an M2 phenotype 68 . These cytokines which are influenced by regulatory T cells and prevent inflammatory processes 69 . Our results showed that the LPS-mediated inflammatory response, including the observed increase in microglial cytokine production, was suppressed by LPC exposure.…”
Section: Discussionmentioning
confidence: 99%